RFID-Based System for Pilgrims Identification and Tracking - Mohandes, Mohamed (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper describes a prototype of a system developed using a passive RFID wristband tag for identification of pilgrims in the holy areas during Hajj. Upon presentation of the tag to a handheld reader all information related to the pilgrim holding the tag will be displayed on the screen of the reader. This way if a pilgrim gets sick, lost, or dies he can be easily identified through the tag on the spot. Officers around the holy area will have a light-weight handheld reader that can get all information from the tag without the need to burden the already overloaded communication network during the Hajj season. The developed prototype was tested on 1000 pilgrims from the country of Ivory Coast in collaboration with officials from Hajj Ministry and Development Commission of the Holy cities of Makkah and Madinah. The results of the experiment have convinced Hajj authorities to utilize this technology for all pilgrims in the future. Additionally, we have explored the possibility of tracking pilgrims using active RFID system. Due to the small number of working tags, experiment was performed only on 6 persons. Results of the latter experiment have shown that the system requires further development and needs to be validated with a larger number of tags.